RANCANGAN SISTEM PERSEDIAAN BAHAN BAKU DENGAN MEMPERTIMBANGKAN WAKTU KADALUARSA DI PT WAHANA INTERFOOD NUSANTARA - Fifi Herni Mustofa; Muhamad Iqbal Syah; Emsosfi Zaini (Teknoin, 2016)
In Indonesia, the development of industry is developing and cause tight competition among companies so that company is prosecuted to work more effective and efficient. PT. Wahana Interfood Nusantara is a process industry that has high production volume characteristics and product standards. Expiration factor is a factor that must be considered for the company, because it greatly affects the quality of the resulting product. The basic model of inventory system used is the inventory model Economic Order Quantity (EOQ). It is developed into an Economic Order Interval (EOI) model with expiration time, as the raw material expiration period is known and the firm minimizes the amount expired by determining fixed material order intervals. Based on the inventory system design considering the minimization of total inventory cost, the company can determine the amount of raw material order and time of ordering.